Synthèse d’entretien avec l’aumônier catholique au niveau de la maison d’arrêt et de correction de MANGA - Tapsoba, Tatiana Nadine (Criminal justice institutions and the social trajectories of adolescents/youth in Burkina Faso: endogenous/local forms and patterns of punishment, 2021)
This summary of an interview with the Catholic chaplain in charge of the Manga prison was conducted on April 28, 2021. During this interview, the participants discussed the typology of misconduct, as well as its management for both modern justice actors and traditional judicial bodies. The interview also looked at the perception of punishment as a function of gender and social class, the meaning of mediation, and collaboration between traditional and modern institutions in the management of misconduct.
Keywords: Administration of Justice; Teenagers; Youth; Punishment; Corrections; Prisons; Manga; Catholic Church; Bishop's Chaplain